An Evaluation of Courses and Fine Arts Activities Organized by the Municipality of Istanbul, Turkey, during the Lifelong Learning Process - (:unkn) unknown (ICLEL CONFERENCES, 2017)
This paper aims to evaluate the courses and art education activities during the lifelong learning process organized by the Municipality of Istanbul for adults. Turkey's Ministry of National Education, local governances and private establishments work on and develop projects for the lifelong learning process, winch was added to objectives of the Bologna Process intended to create a European Higher Education Area. The projects are generally in parallel with the needs of the society and organizations. Two million six hundred people have benefited from the Istanbul Art and Vocation Training Courses (ISMEK) provided by the Metropolitan Municipality of Istanbul between the years of 1996 and 2017. Courses were offered in 540 branches of 35 main branches in 1714 classrooms in 235 course centers of the Metropolitan Municipality of Istanbul. This paper analyzes documents in a qualitative research pattern. In conclusion, the Metropolitan Municipality of Istanbul performs an important function in adult education.
Keywords: ISMEK; Lifelong Learning; Fine Arts Education; Proficiency in Art